Pengaruh Promosi Penjualan “Purchase With Purchase” Terhadap Motivasi Belanja Dan Keputusan Pembelian - Sadana Devica (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
The aim of this study is to analyze the effect of "purchase with purchase" promotion on shopping motivation and consumer purchasing decisions. This research was conducted on 150 respondents by answering the questions posed in the questionnaire which was divided into three case simulations. Analysis of data processing in this study uses a regression method which includes correlationanalysis, t test and F test. The results of processing respondents' answers indicate that "purchase with purchase" promotion has a significant and positive effect on hedonic purchase motivation, utilitarian purchase motivation, and consumer purchasing decisions. In addition, the results of this study indicate that "purchase with purchase" promotions have a greater influence on utilitarian purchase motivation.